2011
DOI: 10.2478/s13386-011-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in natural OSL sensitivity during single aliquot regeneration procedure and their implications for equivalent dose determination

Abstract: Measurement of low temperature (90ºC-120ºC) Thermoluminescence (TL) sensitivity of natural quartz samples subjected to pre-heating and optical stimulation indicate that significant sensitivity changes can occur during measurement of the natural Optically Stimulated Luminescence (OSL). During the measurement of natural signal, the luminescence sensitivity of samples can change by 40%. The sensitivity changes both during the initial preheat and the measurement of natural OSL. The currently used version of Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Negligible difference for sensitivity decrease is observed between PB and WB after the first cycle, suggesting that the sensitivity decrease mainly occurs in the initial measurement cycles, especially between the first and the second cycles. Sensitivity change from the measurement of natural signal to immediately following T x measurement has also been reported for quartz OSL signals (Singhvi et al, 2011).…”
Section: Met-pirir Protocol (110 140 170°c)mentioning
confidence: 71%
See 1 more Smart Citation
“…Negligible difference for sensitivity decrease is observed between PB and WB after the first cycle, suggesting that the sensitivity decrease mainly occurs in the initial measurement cycles, especially between the first and the second cycles. Sensitivity change from the measurement of natural signal to immediately following T x measurement has also been reported for quartz OSL signals (Singhvi et al, 2011).…”
Section: Met-pirir Protocol (110 140 170°c)mentioning
confidence: 71%
“…Sensitivity changes have been investigated during OSL measurement of natural signal in the quartz SAR procedure (e.g. Murray and Wintle, 2000), and it has been reported that sensitivity correction does not take into account the changes in sensitivity that could happen during the readout of the natural signal (Singhvi et al, 2011). It is noted that the luminescence mechanism for these two minerals is significantly different, but for reliable sensitivity correction to be met in the SAR protocol, possible sensitivity changes between L n and T n measurement must be carefully considered for both minerals.…”
Section: Fig 4 Sensitivity Changes Of Wb and Pb As Function Of Measmentioning
confidence: 99%
“…3) the maximum spread in mean of palaeodose distribution of aliquots due to fluctuation in the spatial distribution of beta emitters. 4) ratio of maximum to minimum palaeodoses, which can be used to identify the spread in palaeodoses that arises exclusively due to spatial fluctuation of beta emitters, such that any spread beyond this can be attributed to other factors such as incomplete bleaching and sensitivity changes (Galbraith, 1990;Singhvi et al, 2011). In the following, we quantify the spread in palaeodoses using statistical parameters such as mean, standard deviation and the ratio of minimum to maximum value.…”
Section: Introductionmentioning
confidence: 99%
“…In luminescence dating of sediments, the Single Aliquot Regeneration (SAR) protocol permits palaeodose measurement using single grains and single aliquots (having several grains), (Murray and Wintle, 2000;Singhvi et al, 2011). Several aliquots/grains of a given sample are analyzed to obtain a statistically rigorous palaeodose.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has not considered issues related to changes in OSL sensitivity of the grains between 593 nature and laboratory irradiations; any such changes can be a source of additional intrinsic over-594 dispersion in D e populations (undetected by gamma dose recovery experiments; see, e.g., Stokes,595 1994a, b; Singhvi et al, 2011). But given that there is a satisfactory agreement between the observed 596 OD and the predicted OD (from intrinsic OD and beta dose rate variation), we think this sensitivity 597 change effect must be negligible.…”
Section: A Case Study: the Inter-comparison Sample 555mentioning
confidence: 99%